Education in Canada : in Pursuit of Educational Qualityand Equity - Morgan, Clara (Revista Española de Educación Comparada, 2011)
Canada is one of the few countries in the world that does not have a national department of education but several provincial departments of education which are responsible for educational governance. The article provides an overview of Canada’s educational systems. It describes the current political, economic and social context and provides a brief historical overview oft he evolution of these systems. The article addresses educational quality and equity by drawing on educational indicators and discusses educational reforms that have taken place. The strengths and weak nesses of Canada’s systems of education are analyzed. The article concludes with remarks on the inter-relationship between educational equality and societal inequality Canadá es uno de los pocos países en el mundo que no tienen un Ministerio Nacional de Educación sino numerosos departamentos provinciales que son los responsables de la gestión educativa. El artículo proporciona una panorámica de los sistemas educativos canadienses. Describe el actual contexto político, económico y social y ofrece un breve repaso histórico de la evolución de esos sistemas. El artículo enfrenta la cuestión de la calidad y la equidad educativas a través de indicadores referidos a educación y plantea críticamente las reformas educativas que han tenido lugar. Se analizan los puntos fuertes y las debilidades de los sistemas educativos de Canadá. El articulo concluye con interesantes aportaciones sobre la estrecha relación entre equidad educativa e inequidad social.